Protection of Patient's Autonomy when Undergoing Therapeutic Procedures under the Polish Penal Code - Marek Mozgawa,; Krzysztof Wala, (Medicine, Law & Society, 2022)
This study addresses the issue of criminal liability for performing a therapeutic procedure without patient's consent under the Polish Penal Code of 1997 (Article 192 of the Penal Code). The authors analyse the statutory criteria of the prohibited act concerned. They emphasize the importance of the patient's consent to the legality of therapeutic procedures, and they highlight the situations in which such a procedure may be performed either without the consent or even contrary to the patient's will. The authors conclude that the existence of a separate provision protecting the autonomy of the patient's will deserves approval, although at the same time they advise the need for a certain correction to Article 192 § 1 PC, if only in terms of specifying the entity capable of committing that offence.
Keywords: therapeutic procedure, criminal liability, patient, patient's consent, autonomy of patient's will